Testing and Treating Women after Unsuccessful Conservative Treatments for Overactive Bladder or Mixed Urinary Incontinence: A Model-Based Economic Evaluation Based on the BUS Study. - Ilias Goranitis; Pelham Barton; Lee J Middleton; Jonathan J Deeks; Jane P Daniels; Pallavi Latthe; Arri Coomarasamy; Suneetha Rachaneni; Shanteela McCooty; Tina S Verghese; Tracy E Roberts (PLoS ONE)
Objective To compare the cost-effectiveness of bladder ultrasonography, clinical history, and urodynamic testing in guiding treatment decisions in a secondary care setting for women failing first line conservative treatment for overactive bladder or urgency-predominant mixed urinary incontinence. Design Model-based economic evaluation from a UK National Health Service (NHS) perspective using data from the Bladder Ultrasound Study (BUS) and secondary sources. Methods Cost-effectiveness analysis using a decision tree and a 5-year time horizon based on the outcomes of cost per woman successfully treated and cost per Quality-Adjusted Life-Year (QALY). Deterministic and probabilistic sensitivity analyses, and a value of information analysis are also undertaken. Results Bladder ultrasonography is more costly and less effective test-treat strategy than clinical history and urodynamics. Treatment on the basis of clinical history alone has an incremental cost-effectiveness ratio (ICER) of £491,100 per woman successfully treated and an ICER of £60,200 per QALY compared with the treatment of all women on the basis of urodynamics. Restricting the use of urodynamics to women with a clinical history of mixed urinary incontinence only is the optimal test-treat strategy on cost-effectiveness grounds with ICERs of £19,500 per woman successfully treated and £12,700 per QALY compared with the treatment of all women based upon urodynamics. Conclusions remained robust to sensitivity analyses, but subject to large uncertainties. Conclusions Treatment based upon urodynamics can be seen as a cost-effective strategy, and particularly when targeted at women with clinical history of mixed urinary incontinence only. Further research is needed to resolve current decision uncertainty.